The minimum total heating lander - Dang, Mai Thi (Journal of Computer Science and Cybernetics, 2015)
The article will research a lander flying into the atmosphere with flow velocity constraint, i.e. the total load by means of minimizing the total thermal energy at the end of the landing process. The lander’s distance at the last moment depends on the variables selected from the total thermal energy minima. To deal with the problem, the  Pontryagin maximum principle and scheme Dubovitskij Milutin will be applied. Boundary value problems are solved by the introduction and continuation of the perturbation parameters and solutions for the selected parameter. The results of simulations are performed on Matlab.